CAP and the Caribbean - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
The single European Market of 1992 poses challenges and opportunities for the countries of the Caribbean. The recent performance of Caribbean agriculture indicates the problems to be surmounted in EEC-Caribbean trade and cooperation arrangements....